PENGARUH DISIPLIN DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS XI IPS DI SMAN 1 MINAS - Sherly Motavany; Suarman Suarman; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to analyze the effect, discipline of learning and learning motivation on student achievement in economic subjects in class XI IPS at SMAN 1 Minas. This research uses quantitative methods. The data collection process begins with collecting data as a whole from field research and library research. The data analysis technique used is multiple linear regression test with the help of SPSS version 20.0. The results showed that partially there was an effect of student learning discipline and student learning motivation on student achievement in economics class X1 at SMA Negeri 1 Minas on learning achievement. Simultaneously all independent variables have an effect on student achievement in economics class X1 at SMA Negeri 1 Minas. The amount of influence of the independent variables (X1) and (X2), namely discipline and motivation, can affect the Y variable (learning achievement) only 22.7%. While 77.3% is influenced by other variables not examined in this studyKey Words: Learning Discipline, Learning Motivation, Learning Achievement